Design and Experimental Evaluation of a Fruits Hybrid-Solar Dryer - TOSSA, Kossoun Alain (My University, 2023)
In this work a hybrid solar dryer is designed and its performance is experimentally evaluated. The user can set the drying parameters regarding the fruits to dry, and after the drying process started it can last a 12-hour drying cycle. It is designed to have maximum storage capacity of 10 kg. It can be configured to operate within the temperature range recommended for drying the product present. Two electrical sources (solar photovoltaic and conventional electricity) supplied the control system. This control system ensures the permanent presence of one of the two additional thermal sources (i e., the heating resistors and the energy gas). This makes it possible to obtain and maintain the recommended temperature range in the drying chamber. The simulation of the airflow distribution inside the device was performed with ANSYS Fluent software for the solar thermal mode and in case of an empty drying chamber. It showed that the drying-air is well distributed in the drying chamber and that the temperature inside the drying chamber is around 60°C. The performance tests, in a real environment (empty drying chamber and with loaded drying chamber), are used to validate the results of the simulations carried out and to assess the operation of the control system for a temperature range of 45 to 60°C. The maximum temperature reached in natural convection when the dryer is empty is 56.7°C. Tests made on pineapples slices showed that the dryer can reduce water from 80-86% to 6% in 12h. The use of this dryer will not only make it possible to carry out drying at any time of the day, but will also help to reduce the drying time of the products, while preserving their nutritional values.
Keywords: Hybrid Solar Dryer; Modelling; Simulation; Fruit Drying; ANSYS Fluent